Role of Nucleocytoplasmic RNA Transport during the Life Cycle of Retroviruses - Shida, Hisatoshi (Frontiers in Microbiology, 2012)
Retroviruses have evolved mechanisms for transporting their intron-containing RNAs (including genomic and messenger RNAs, which encode virion components) from the nucleus to the cytoplasm of the infected cell. Human retroviruses, such as human immunodeficiency virus (HIV) and human T cell leukemia virus type 1 (HTLV-1), encode the regulatory proteins Rev and Rex, which form a bridge between the viral RNA and the export receptor CRM1. Recent studies show that these transport systems are not only involved in RNA export, but also in the encapsidation of genomic RNA; furthermore, they influence subsequent events in the cytoplasm, including the translation of the cognate mRNA, transport of Gag proteins to the plasma membrane, and the formation of virus particles. Moreover, the mode of interaction between the viral and cellular RNA transport machinery underlies the species-specific propagation of HIV-1 and HTLV-1, forming the basis for constructing animal models of infection. This review article discusses recent progress regarding these issues.